Peningkatan Hasil Belajar IPAS Materi Bumiku Sayang Bumiku Malang Melalui Pendekatan Berdiferensiasi Proses pada Peserta Didik Kelas V SDN Dukuh Kupang II Surabaya - Eva Mulia Agustin; Bekti Wirawati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to implement differentiated learning processes (Learning Styles) to improve learning outcomes in the IPAS subject on the topic "Bumiku Sayang Bumiku Malang" for fifth-grade students at SDN Dukuh Kupang II Surabaya. This research is a classroom action study that involves three differentiated learning styles: visual, audiovisual, and kinesthetic. The research was conducted at SDN Dukuh Kupang II Surabaya with the subjects being fifth-grade students, totaling 28 participants. This research is divided into two cycles (Cycle I and II), starting with the stages of planning, implementation, observation, evaluation, and reflection. The data collection techniques in this research use observation, interviews, documentation, and tests. The results of this study indicate an improvement in learning outcomes in IPAS on the topic "Bumiku Sayang Bumiku Malang" through differentiated process learning in the fifth grade at SDN Dukuh Kupang II Surabaya. In the initial pre-cycle activities, the percentage of student mastery was 35%, then in Cycle I it increased to 60%, and in Cycle II it rose again to 85%.